Comparison of Safety Factor Evaluation Methods for Flexural Buckling of HSS Welded Box Section Columns. (August 2018) - Kövesdi, B.; Somodi, B.
Abstract: The statistical evaluation of the experimental and numerical results is an essential task in case of resistance model development for civil engineering structures. If a design model is developed which has analytical or empirical background, its safety level has to be confirmed and it should be proved that the developed design method fits the safety requirements of the EN 1990 [1]. However, in the EN 1990 and also in the international literature there are several different safety factor evaluation methods that can be used to check the necessary safety level of the analyzed design method (e.g.: 5% quantile level, 2.3% quantile level, 1‰ quantile level, γM partial safety factor, γM ⁎ partial safety factor, β reliability index). In the international literature different calculation methods can be found even for the calculation of the same partial safety factor as well. In the present study the flexural buckling resistance of high strength steel (HSS) welded box sections is analyzed and the application of different safety approaches are demonstrated and compared. The authors investigated the buckling resistance of the analyzed columns by laboratory tests and by numerical simulations and the necessary partial safety factors are determined by different approaches. Based on the comparison tendencies are identified and the differences between the statistical evaluation methods are demonstrated.